Przestrzenie tożsamości - Kosowska, Ewa (Er(r)go. Teoria - Literatura - Kultura, 2003)
Ewa Kosowska "The Spaces of Identity" "The Spaces of Identity" explores the problematic status of identity and some of its postmodern implications. Kosowska discusses the emergence of this notion in the discourse of Western science, its dependence on linguistic determinants and its relation to the notion of difference/differance. She identifies the beginnings of contemporary interest in identity with the development of non-Euclidean geometry and philosophical reflection inspired by Husserl's and Heidegger's phenomenology. Kosowska argues that identity has become a notion which is responsible for constituting beings. Thus it is necessary to pose the question where identity exists. Does it exist in time or in space? Either answer wil leave us with many problems unsolved. However, the category of identity may function as an approximation which signals a postulated and idealised relation dependent on the kind of human perception and cultural principles of classifying phenomena.